Fellowship of the Spring: An initiative to document and protect the world's oases - Roderick J. Fensham; Rouhollah Adinehvand; Sally Babidge; Marco Cantonati; Matthew Currell; Linda Daniele; Alper Elci; Diana M.P. Galassi; África de la Hera Portillo; Salah Hamad; Dongmei Han; Hussain Ali Jawadi; et al. (Science of The Total Environment, 2023)

Urgent plea for global protection of springs - Marco Cantonati; Roderick J. Fensham; Lawrence E. Stevens; Reinhard Gerecke; Douglas S. Glazier; Nico Goldscheider; Robert L. Knight; John S. Richardson; Abraham E. Springer; Klement Tockner (Conservation Biology, 2021)

Mechanisms behind persistence of a fire-sensitive alternative stable state system in the Gibson Desert, Western Australia - Boyd R. Wright; David E. Albrecht; Jennifer L. Silcock; John Hunter; Roderick J. Fensham (Oecologia, 2019)

To what extent is drought‐induced tree mortality a natural phenomenon? - Roderick J. Fensham; Boris Laffineur; Craig D. Allen (Global Ecology and Biogeography, 2019)
Aim Catastrophic forest mortality due to more extreme rainfall deficits and higher temperatures under future climate scenarios has been predicted. The aim of this study is to explore the magnitude of historical drought‐induced tree mortality under pre‐warming conditions. Location North‐eastern Australia. Time period 1845–2017. Major taxa studied Trees. Methods Field survey, historical analysis and climate analysis. Results We present evidence of 18%–30% tree mortality from recent droughts across three regions of north‐eastern Australia with rainfall deficits less severe than earlier historical droughts. The corrected temperature record represents modest warming at the stations with long records in the vicinity of the study areas. In terms of rainfall deficit the most severe drought on record occurred in the early 20th century, and historical evidence confirms that this drought and earlier droughts before the advent of pastoralism coincided with substantial tree mortality. Main conclusions Dramatic declines in woody biomass in response to drought historically occurred more than once a century and are a natural phenomenon in semi‐arid Australia. The magnitude of drought‐induced tree mortality under natural climate fluctuations requires further investigation in other continents. Widespread drought‐induced tree mortality is not just a recent global change phenomenon and has been underestimated as a natural ecological process. However, even more severe forest die‐off events from more extreme hotter droughts are predicted if Earth’s warming proceeds as currently projected.

Can environmental tolerances explain convergent patterns of distribution in endemic spring snails from opposite sides of the Australian arid zone? - Renee A. Rossini; Hannah L. Tibbetts; Roderick J. Fensham; Gimme H. Walter (Aquatic Ecology, 2017)

Dominant tree species are at risk from exaggerated drought under climate change - Roderick J. Fensham; Josie Fraser; Harry J. MacDermott; Jenifer Firn (Global Change Biology, 2015)
Predicting the consequences of climate change on forest systems is difficult because trees may display species‐specific responses to exaggerated droughts that may not be reflected by the climatic envelope of their geographic range. Furthermore, few studies have examined the postdrought recovery potential of drought‐susceptible tree species. This study develops a robust ranking of the drought susceptibility of 21 tree species based on their mortality after two droughts (1990s and 2000s) in the savanna of north‐eastern Australia. Drought‐induced mortality was positively related to species dominance, negatively related to the ratio of postdrought seedlings to adults and had no relationship to the magnitude of extreme drought within the species current geographic ranges. These results suggest that predicting the consequences of exaggerated drought on species’ geographic ranges is difficult, but that dominant species like Eucalyptus with relatively slow rates of population recovery and dispersal are the most susceptible. The implications for savanna ecosystems are lower tree densities and basal area.

How does clay constrain woody biomass in drylands? - Roderick J. Fensham; Don W. Butler; Jenny Foley (Global Ecology and Biogeography, 2015)
Aim To investigate the role of clay in limiting the development of woody biomass in drylands. Location A ustralia. Methods Spatial data representing woody biomass, soil clay content and climate for the A ustralian continent were interpreted to explore the relationship between a moisture index and woody biomass on clay and non‐clay substrates. Moisture and soil water potential were investigated through time for clay and sand plains. Sub‐soil clay and other soil characteristics were compared between areas with and without high tree mortality after drought. Results The substantially lower woody biomass on clay soils than non‐clay soils in the drylands of the A ustralian continent verifies the inverse texture effect. A clay floodplain consistently held more water than an adjacent sandplain, but soil moisture in the clay was effectively inaccessible to plants for much longer periods because of more negative values of water potential in the clay soil. Small increases in sub‐soil clay were associated with high tree mortality. Main conclusions Our findings suggest that the ‘inverse texture effect’, which describes the negative association of woody biomass with soil clay content in drylands, may mostly relate to the moisture‐retentive properties of clay rather than being caused by reduced infiltration and enhanced evaporation from clay‐rich soils. Our evidence suggests that clay soils constrain woodiness in drylands by exacerbating water stress, and confirm the fundamental role of aridity in determining woody biomass and the global distribution of grassland.

Specialized and stranded: habitat and biogeographical history determine the rarity of plant species in a semi‐arid mountain range - Jennifer L. Silcock; Roderick J. Fensham (Journal of Biogeography, 2014)
Aim We examined patterns of rarity in the flora of a semi‐arid mountain range with a high concentration of rare species and 150 years of elevated grazing pressure, to establish the influences of habitat specialization, species biology, biogeography and grazing pressure in determining the distributions and abundances of species. Location Grey Range and associated Tertiary sandstone ranges, eastern semi‐arid Australia. Methods We characterized the major habitats by soil and vegetation parameters, and surveyed 647 sites across seven habitat units to determine the probability of occurrence of 19 rare species. We then analysed the occurrence of rare plants in relation to species biology (dispersal characteristics, flowering, fruiting and recruitment frequency), grazing pressure and, for the barren plateaux, their size and isolation. Results Rare species were found to be concentrated in three restricted habitat types – barren plateaux, gidgee toeslopes and sheltered habitats – which are clearly separated from other habitats in land‐form, soil properties and floristics. Larger barren plateaux were more likely to harbour rare species, but there was no correlation between plateau isolation and the incidence of rare plants. No species seemed to be limited by low seed production, but barren‐plateau shrubs recruited only infrequently. Only two species were adapted to long‐distance dispersal, meaning that most are effectively stranded in their insular habitats. Although five perennial shrub species were heavily grazed, there were no significant relationships between the distance to water and the occurrence of rare plants. Main conclusions Habitat specialization, reproductive biology and biogeographical history interact to create the observed patterns of rarity in this semi‐arid mountain range. There is no evidence that any species have become rare or restricted as a result of grazing pressure. Species confined to plateaux, sheltered habitats and gidgee toeslopes represent relictual populations, and the association of rare plants with larger plateaux suggests that local extinctions were more likely on smaller plateaux during Pleistocene climatic fluctuations.

Aborigine‐managed forest, savanna and grassland: biome switching in montane eastern Australia - Don W. Butler; Roderick J. Fensham; Brett P. Murphy; Simon G. Haberle; Sarah J. Bury; David M. J. S. Bowman (Journal of Biogeography, 2014)
Aim To assess hypotheses about the role of anthropogenic fire in the maintenance and origin of a fine‐scale vegetation mosaic of rain forest, eucalypt savanna and grassland. Location Bunya Mountains, subtropical eastern Australia. Methods A time series of vegetation maps was compiled from historical and recent aerial photography and field surveys. Geospatial models were constructed of environmental domains for rain forest, savanna and grassland, and for areas of biome change. Grassland soils were analysed for carbon isotope ratios (δ 13 C), and radiocarbon ( 14 C) dates were acquired for bulk samples from a range of depths. Results Analysis revealed weak associations between topography and the distribution of rain forest, savanna and grassland, and their patterns of recent change. Grassland occupied an environmental domain intermediate between rain forest and savanna and was more than four times as likely to occur within a matrix of rain forest rather than savanna. There was a large proportional reduction in the area of both grassland (−35%) and savanna (−19%) between 1961 and 2006 because of the expansion of rain forest. However, the greater initial extent of savanna meant that the areal loss of savanna was an order of magnitude greater than for grassland (1433 vs. 146 ha). There was no evidence of abrupt changes in δ 13 C in grassland soil profiles, indicating stability of the vegetation over the last 2000 years. Main conclusions There is no simple gradient in ‘tree suitability’ from rain forest, through savanna, to treeless grassland on the Bunya Mountains. A general absence of fire since the 19th century has greatly reduced the extent of grassy savanna and grassland formations, to the advantage of rain forest. These results support the hypothesis that the vegetation mosaic on the Bunya Mountains is a cultural artefact and testament to millennia of skilful and persistent burning. We could not conclusively reject the hypothesis that the grasslands are Pleistocene relicts that have declined throughout the Holocene; nonetheless, an explanation more consistent with the evidence overall is that the grasslands must have had periods of expansion during the Holocene, probably as a consequence of severe fires that have destroyed patches of rain forest.

Fire regimes of A ustralia: a pyrogeographic model system - Brett P. Murphy; Ross A. Bradstock; Matthias M. Boer; John Carter; Geoffrey J. Cary; Mark A. Cochrane; Roderick J. Fensham; Jeremy Russell‐Smith; Grant J. Williamson; David M. J. S. Bowman (Journal of Biogeography, 2013)
Aim Comparative analyses of fire regimes at large geographical scales can potentially identify ecological and climatic controls of fire. Here we describe A ustralia's broad fire regimes, and explore interrelationships and trade‐offs between fire regime components. We postulate that fire regime patterns will be governed by trade‐offs between moisture, productivity, fire frequency and fire intensity. Location Australia. Methods We reclassified a vegetation map of A ustralia, defining classes based on typical fuel and fire types. Classes were intersected with a climate classification to derive a map of ‘fire regime niches’. Using expert elicitation and a literature search, we validated each niche and characterized typical and extreme fire intensities and return intervals. Satellite‐derived active fire detections were used to determine seasonal patterns of fire activity. Results Fire regime characteristics are closely related to the latitudinal gradient in summer monsoon activity. Frequent low‐intensity fires occur in the monsoonal north, and infrequent, high‐intensity fires in the temperate south, demonstrating a trade‐off between frequency and intensity: that is, very high‐intensity fires are only associated with very low‐frequency fire regimes in the high biomass eucalypt forests of southern A ustralia. While these forests occasionally experience extremely intense fires (> 50,000 kW m −1 ), such regimes are exceptional, with most of the continent dominated by grass fuels, typically burning with lower intensity ( −1 ). Main conclusions Australia's fire regimes exhibit a coherent pattern of frequent, grass‐fuelled fires in many differing vegetation types. While eucalypts are a quintessential A ustralian entity, their contribution as a dominant driver of high‐intensity fire regimes, via their litter and bark fuels, is restricted to the forests of the continent's southern and eastern extremities. Our analysis suggests that the foremost driver of fire regimes at the continental scale is not productivity, as postulated conceptually, but the latitudinal gradient in summer monsoon rainfall activity.